E-134 Treatment of cerebral aneurysms with the fred jr flow-diverting stent: a case series and meta-analysis. (23rd July 2022) - El Naamani, K; Al Saeigh, F; Chen, C; Abbas, R; Sioutas, G; Amllay, A; Shehabeldine, M; Gooch, M; Herial, N; Jabbour, P; Rosenwasser, R; Tjoumakaris, S
Abstract : Background: With the development of the Flow Re-Direction Endoluminal Device Junior (FRED Jr), treatment of distal aneurysms and/or aneurysms with small parent vessels has become a viable option. Objectives: To assess the efficacy and safety of FRED Jr in the treatment of distal aneurysms with small parent vessels. Methods: This is a single center retrospective study and meta-analysis of patients treated with FRED Jr for intracranial aneurysms. The primary outcome was complete aneurysm occlusion at final follow-up. Secondary outcomes included stroke rates, mortality rates, need for retreatment and clinical outcomes. Results: There were a total of 7 patients with 7 aneurysms treated with FRED Jr. Mean aneurysm neck, width, height, and parent artery diameter were 2.6±0.8 mm, 3.1±0.9 mm, 2.5±1.0 mm, and 1.8±0.6 mm respectively. The complete occlusion rate was 40% at 6 months, and favorable outcome (mRS 0–2) was observed in all patients in follow-up. Stroke complication occurred in none of the patients. Seven studies from 1, 360 articles were identified for inclusion in the meta-analysis, comprising 227 patients with 244 aneurysms treated with FRED Jr. Mean aneurysm height, width, neck and parent artery diameter were 6.9±3.3 mm (pooled=5.6 [<0.1–11.47] mm), 6.6±2.2 mm (pooled=6.6 [4.2–9.1] mm), 4.4±1.4 mm (pooled=4.1 [3.3 -4.9] mm), and 2.0±0.2mm (pooled=2.1 [1.7–2.5]), respectively. At final follow-up, the pooled complete occlusion and complication rates were 69.9% and 0%, respectively. Conclusion: FRED Jr demonstrated moderate efficacy and good safety in the treatment of distal aneurysms with small parent vessels at mid-term follow-up. Disclosures: K. El Naamani: None. F. Al Saeigh: None. C. Chen: None. R. Abbas: None. G. Sioutas: None. A. Amllay: None. M. Shehabeldine: None. M. Gooch: 2; C; Stryker. N. Herial: None. P. Jabbour: 2; C; Medtronic, Microvention, Balt, Cerus Endovascular. R. Rosenwasser: None. S. Tjoumakaris: 2; C; Microvention, Medtronic.